Karyological Studies on Tho-tho (Bos indicus): an Indigenous Cattle of Nagaland - Longkumer, I.; Yenisetti, S. C.; Mukherjee, A.; Mukherjee, S.; Mech, M.; Rongmei, J.; Rajkhowa, C. (International Journal of Bio-resource and Stress Management, 2023)
Tho-tho cattle is short to medium stature black color animal available in different hilly pockets of Nagaland. Body is mostly covered with short and glossy hairs. Coat color is either pure black or skew bald, neck is long and fine, horns are curved with tips pointed upward. Udder is small and hump is prominent in this animal. Tho-tho cattle play an important role in the socio-cultural life of the local tribal people and are considered as the ceremonial animal of various social rituals. The diploid chromosome number in Tho-tho cattle was observed to be 60 in all complete metaphase spreads. The normal karyotype of Tho-tho cattle showed that all the autosomes are acrocentric whereas among the sex chromosome X was found to be sub-metacentric and Y as smallest acrocentric. The relative length of the autosomal chromosomes varied from 5.24% of chromosome number 1 to 1.88% of chromosome number 29 and the relative length of the X and Y chromosomes were 4.91 and 1.79%, respectively. The average centromeric index in Tho-tho cattle was about 36.18% and the arm ratio was 1.78.